The Development of Analytical Reading and Thai Literary Criticism Skills Using Panorama Reading Instruction Combined with Graphic Organizers Among Mathayom 3 Students at Inburi School, Sing Buri Province - Kumpiree, Supasinee; Arpakulanu, Suksawas (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2025)
This study aimed to: 1. compare the analytical reading and Thai literary criticism skills of Grade 9 (Mathayom 3) students before and after instruction using the Panorama reading approach combined with graphic organizers; and 2. assess students’ satisfaction with the instructional approach. The sample consisted of 34 students from Class 3/5 at Inburi School during the first semester of the 2024 academic year, selected through simple random sampling with classrooms as the sampling unit. Research instruments included 10 lesson plans, a 30-item multiple-choice analytical reading skills test, and a 12-item satisfaction questionnaire. Data were analyzed using mean, standard deviation, and dependent samples t-test. The findings revealed that: 1. students’ analytical reading and Thai literary criticism skills significantly improved after instruction using the Panorama reading approach combined with graphic organizers, with statistical significance at the 0.05 level; and 2. students’ overall satisfaction with the instructional approach was rated at a high level.